Parametric and Kinetic Study of Silicon Nitride Film Deposition on Silicon Wafer by Low Pressure Chemical Vapor Deposition (LPCVD) Method - Velasco, Angelito A. (Philippine Engineering Journal; Vol 23 No 1 (2002), 2011)
Silicon nitride films were deposited on silicon wafers by Low-Pressure Chemical Vapor Deposition (LPCVD) method. Reaction gases were ammonia and 20% silane in nitrogen. The effects of (A) deposition temperature, (B) chamber pressure , (C) NH3-SiH4 flowrate ratio and (D) deposition time on the thickness of the film produced were studied using a full 2k factorial design. The film thickness was found to increase proportionally with temperature, pressure and time, and inversely with NH3-SiH4 flowrate ratio. Analysis of variance (ANOVA) shows that all main effects and interactions AC, AD, and CD were statistically significant at 99% confidence level. An interactive first order model was fitted to the experimental data: Y = 158.46 + 70.39X1 +26.86X2 – 66.44X3 + 74.45X4 –29.3X1X3 + 33.35X1X4– 30.68X3X4 A kinetic study was also conducted in order to determine the rate equation for the growth of silicon nitride on silicon. The computed activation energy was 21.454 kcal/mol, which indicates that the surface reaction is rate limiting. The rate equation was: Deposition rate, nm/min = 37661.7 exp (-4578.5/T). Scanning electron micrographs show that the silicon nitride deposits appear as spherical-cap shaped clusters. Energy dispersive x-ray (EDX) and x-ray diffraction (XRD) analyses confirm the formation of silicon nitride.